O KONSTYTUCJACH CESARSKICH - 4 tytuł 1 księgi Digestów. Tekst - tłumaczenie - komentarz - Tarwacka, Anna (Zeszyty Prawnicze, 2017)
O KONSTYTUCJACH CESARSKICH - 4 tytuł 1 księgi Digestów. Tekst - tłumaczenie - komentarz